A Design and Optimization of Circular Microstrip Patch Antenna at 2.4 GHz for Different Wireless Applications - H. Khidhir, Ali (Al-Nahrain Journal of Science, 2022)
In this paper, the required antenna was designed and simulated using mathematical equations and algorithms for the maximum accuracy of the required frequency. As well as using the MATLAB programming language to program and design a graphical interface that calculates the basic measurements required by the graphical user interface development environment (GUIDE) for the required antenna design. Also, the use of computer simulation technology software for the simulation process to design the required model and test it virtually before implementation. As a result, the most important parameters that describe the quality and efficiency of the antenna used were calculated and studied. These parameters are return loss, standing wave voltage ratio, input impedance which are very important for antenna work, frequency bandwidth of the signal used. These values are -47.008702 dB, VSWR of 1.0089659, input impedance of 50.233036 Ω, and bandwidth of 51.4 MHz (ranging from 2.3747 to 2.4261 GHz) respectively, which operating at 2.4 GHz for the resonant frequency used.